Mothers and Workers in the Time of COVID-19: Negotiating Motherhood within Smart Working. (October 2022) - Rania, Nadia; Parisi, Rosa; Lagomarsino, Francesca
The article is an autoethnographic account written by three Italian academic researchers and mothers with children of different ages. The authors engage in a reflection starting with their experience as working women committed to the work–family negotiation process while facing the COVID-19 health emergency that has affected the whole world. This article focuses on how we, as middle-class, heterosexual, white mothers working in a privileged employment context during the period of the pandemic lockdown, negotiated the complex mother and worker roles, balancing work and family time while smart working (teleworking from home). We start with a reflection on the use of autoethnography as a research tool and then propose an analysis of work–family balance strategies in an anomalous situation, such as that of the lockdown, highlighting the tensions in gender roles within dual-career families.